Haemoglobin Lepore in a Malay Family: A Case Report - Pasangna, J.; George, E.; Nagaratnam, M. (Malaysian Society of Pathologists, 2005)
A 2-year-old Malay boy was brought to the University Malaya Medical Centre for thalassaemia screening. Physical examination revealed thalassaemia facies, pallor, mild jaundice, hepatomegaly and splenomegaly. Laboratory investigations on the patient including studies on the parents lead to a presumptive diagnosis of homozygous Haemoglobin Lepore (Hb Lepore). The aim of this paper